Cognitive frailty in relation to vitamin B12 and 25-hydroxyvitamin D in an elderly population: a cross-sectional study from NHANES - Pan, Yu; Tang, Xue Yin; Yang, Juan; Feng, Zhu Qing; Yuan, Yan; Jiang, Yi; Hu, Gui Ming; Dong, Jiang Chuan (Frontiers in Nutrition, 2024)
Background: Nutritional support has been identified as a potential intervention for cognitive frailty; however, the association between 25-hydroxyvitamin D (25-(OH)D), vitamin B12, and cognitive frailty remains ambiguous.Methods: This study utilized data from two cycles (2011)(2012)(2013)(2014) of the National Health and Nutrition Examination Survey (NHANES) to investigate this relationship. The researchers constructed a 41-item frailty index encompassing diverse aspects of physical functioning, psychological evaluation, and medical conditions, and evaluated each participant individually. The study utilized Spearman's rank correlation coefficient and univariate ordered logistic regression to assess the relationships between variables and cognitive frailty. Recursive feature elimination and cross-validation methods were employed to identify the most influential variables for building and optimizing multivariate ordered logistic regression models. Subgroup analyses and interaction tests were further conducted to validate the identified correlations.The findings of this study confirm a negative linear correlation between 25-(OH)D levels and cognitive frailty in older adults. Specifically, a one-unit increase in 25-(OH)D levels was associated with a 12% reduction in the risk of cognitive frailty. The result was further supported by subgroup analyses and interaction tests.The existence of a negatively correlated linear association between 25-(OH)D levels and cognitive frailty in older adults is plausible, but further rigorously designed longitudinal studies are necessary to validate this relationship.